Evolution of consumption and livelihood impacts from cash and food transfer programs: Eight-year post-program experimental evidence from Bangladesh - Ahmed, Akhter; Bakhtiar, M. Mehrab; Hidrobo, Melissa; Hoddinott, John F.; Rakshit, Deboleena; Roy, Shalini (International Food Policy Research Institute, 2025)
Findings from this study will provide greater insight as to how and why transfer programs have mixed post-intervention effects across different contexts, and how gender and livelihood opportunities may influence these trajectories. These insights will help inform the future design of transfer programs that aim to support sustainable poverty reduction and gender-equitable livelihoods, including to guide modifications tailored to the local context.